Religion and politics in contemporary Japan : Soka Gakkai youth and Komeito - Fisker-Nielsen, Anne Mette (Japan anthropology workshop series., 2012)
Presenting a study of politics at grassroots level among young Japanese, this book examines the alliance between the religious movement Soka Gakkai (the 'Value-creation Society') and Komeito (the 'Clean Government Party'), which shared power with the Liberal Democratic Party from 1999 to 2009. Drawing on primary research carried out among Komeito supporters, the book focuses on the lives of supporters and voters in order to better understand the processes of democracy. It goes on to discuss what the political behaviour of young Komeito supporters tell us about the role of religious organiza.